YOUTUBE AS A MEDIA FOR STUDENTS’ COMPREHENSIVE LISTENING ABILITY AT JUNIOR HIGH SCHOOLS IN BEKASI - Sigit Widiyarto; Mulyadi Mulyadi; Lusiana Wulansari; Aster Pujaning Ati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
Learning in the listening aspect is still difficult for middle and upper level students. This is a consequence of weak vocabulary, structure, and speaking skills. Comprehensive listening skills are often complained by some students. It needs improvement and learning innovation in the current century. This study aimed to determine whether there was an increase in learning outcomes after utilizing youtube as a learning media, how big the impact was and how the learning process using you tube media was. This study used an experimental method of pretest and posttest only. Respondents were 35 students of SMP Alikhlas class VI Bekasi. The data were taken from the test before and after being given treatment using YouTube media. The data were processed with SPSS 20 and then tested for normality and homogeneity first, then processed using a paired sample test. The results showed that there was an increase of 12.2941. The use of youtube improved listening skills. Utilizing Youtube included looking for material/information, watching and listening to material, analyzing and distributing material to students and teachers. The recommendation was that teachers could try to provide the widest possible time and space for students to improve their abilities independently, including using YouTube in learning. Consistent evaluation and supervision is the key to the success of learning using youtube media.